Staphylococcus aureus: Screening for Nasal Carriers in a Community Setting with Special Reference to MRSA - Yukti Sharma; Sanjay Jain; Harshvardhan Singh; Vasudha Govil (Scientifica)
Introduction. Emergence of MRSA infections among previously healthy persons in community settings (without exposure to health care facilities) has been noted recently. MRSA infections are now classified as health care-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA) infections. Its colonization is an important risk factor for subsequent MRSA infection. Aims and Objectives. The aim was to screen patients and health care workers for staphylococcal carriage, identify risk factors for MRSA colonization, and determine the sensitivity pattern. Materials and Methods. A total of 200 subjects were screened for nasal carriage after obtaining verbal consent. These were both healthy subjects attending various outpatient departments and health care workers. Specimens were collected from the anterior nares using premoistened sterile cotton swabs and inoculated onto blood agar and mannitol salt agar and incubated at 37°C for 24–48 h. Results. Staphylococcus aureus colonisation was found to be 12% (n=24). MRSA was identified in 5% (n=10) which represents 41.66% of SA. A total of 10 strains of MRSA were isolated from 200 subjects, giving an overall positivity rate of 5%. Discussion. Staphylococcal colonization was found to be 12% (MRSA 5%). Fluoroquinolone resistance was remarkable whereas all strains were sensitive to vancomycin, teicoplanin, linezolid, quinupristin-dalfopristin.